Management of fever, hyperglycemia, and swallowing dysfunction following hospital admission for acute stroke in New South Wales, Australia. Issue 1 (10th November 2013) - Drury, Peta; Levi, Christopher; McInnes, Elizabeth; Hardy, Jennifer; Ward, Jeanette; Grimshaw, Jeremy M.; D' Este, Catherine; Dale, Simeon; McElduff, Patrick; Cheung, N Wah; Quinn, Clare; Griffiths, Rhonda; et al.
<x xml:space="preserve">Abstract</x> Background Fever, hyperglycemia, and swallow dysfunction poststroke are associated with significantly worse outcomes. We report treatment and monitoring practices for these three items from a cohort of acute stroke patients prior to randomization in the Quality in Acute Stroke Care trial. Method Retrospective medical record audits were undertaken for prospective patients from 19 stroke units. For the first three‐days following stroke, we recorded all temperature readings and administration of paracetamol for fever (≥37·5°C) and all glucose readings and administration of insulin for hyperglycemia (>11 mmol/L). We also recorded swallow screening and assessment during the first 24 h of admission. Results Data for 718 (98%) patients were available; 138 (19%) had four hourly or more temperature readings and 204 patients (29%) had a fever, with 44 (22%) receiving paracetamol. A quarter of patients (n = 102/412, 25%) had six hourly or more glucose readings and 23% (95/412) had hyperglycemia, with 31% (29/95) of these treated with insulin. The majority of patients received a swallow assessment (n = 562, 78%) by a speech pathologist in the first instance rather than a swallow screen by a nonspeech pathologist (n = 156, 22%). Of those who passed a screen (n = 108 of 156, 69%), 68% (n = 73) were reassessed by a speech pathologist and 97% (n = 71) were reconfirmed to be able to swallow safely. Conclusions Our results showed that acute stroke patients were: undermonitored and undertreated for fever and hyperglycemia; and underscreened for swallowing dysfunction and unnecessarily reassessed by a speech pathologist, indicating the need for urgent behavior change.